Analysis of Habit Patterns in Academic Behavior in Student Learning Discussions - Mila Zulfa, Maulida Noor; Setiawan, Deka; Fardani, Much Arsyad (International Journal of Elementary Education, 2020)
The discussion method can encourage inactive students to be active and confident, but there are still some students who are not able to cooperate well. This study aimed to analyze the pattern of academic behavior habits in the learning discussion of grade 4 students. The population in this study was all grade 4 students at SD 5 Karangbener totaling 24 students including 15 girls and 9 boys. This research used data collection techniques including the stages of observation, interviews and field notes. This study used descriptive qualitative data analysis method. The results of the analysis of students 'academic behavior during the learning discussion were the classification of student behavior during discussion including praying before the lesson began, paying attention to the teacher's explanation, making material summaries, being on time in doing assignments, participating in discussions, daring to express opinions, respecting other students' opinions, writing the results of the discussion, conveying the results of the discussion confidently, reading diligently, enthusiastically taking part in learning, concentration during the learning process, diligently working on the exercises, daring to ask questions while having difficulty doing the exercises. The academic behavior of fourth grade students of SD 5 Karangbener was included in very good interpretations with behavioral indicators that have been found based on field data. The discussion method has a positive academic impact on students which can be viewed from the cognitive, affective, and psychomotor domains.